APLIKASI LIMBAH BAN DALAM PADA PRODUK SKATEBOARD CARRIER - Mukti, Agung Cahyo; Prasetya, Rahmawan D.; Suminto, Sekartaji (Ide dan Dialog Desain Indonesia (Idealog), 2023)
Every year, the number of vehicle tires production increases with market demand. The Indonesian Rubber Council (Dekarindo) reports that the production of car tires in Indonesia from 2010 to 2011 reached 14.4 to 15.4 tons per day, and the total production of motor vehicle tires reached150. 2 units in 2019. This can be considered as the amount of prohibited waste and environmental problems due to waste. This design project aims to develop a skateboard carrier design that is multifunctional and in accordance with user needs, as a development of a unique material that has its own charm in the world of fashion design, especially bags, and also as an ef ort to utilize or treat tire waste in a safe and secure manner. environmentally friendly using the upcycle method. This product design is intended for people interested in skateboarding, both men and women, with an age range of 17 to 35 years or a height of 160 to 175 cm. This process involves aspects of efficiency and ergonomics. Keywords: Skateboard Carrier, Skateboarding, Upcycle, Bag, Inner Tube Waste